UTILIZATION OF ASPIRATION FUND OF AMBON CITY LEGISLATIVE COUNCIL IN HATIVE BESAR, TELUK AMBON DISTRICT - Rukoyah (Media Inovasi Pendidikan dan Publikasi, 2023)
DPRD members carry out their role for the community in accordance with their obligations to accommodate, follow up on all aspects of complaints in the community. Parliament in the region, in this case the DPRD, is a representative body of the people domiciled in the region. DPRD is a representative body of the people and is an element of government in the region that has the task of making local regulations and absorbing the aspirations of the people and accommodating the aspirations of the people who have elected them. The current political reality suggests that elected candidates (members of the City/Regency DPRD) must absorb aspirations by utilizing recess and working visits to the electoral districts. There is no reason for DPRD members not to absorb and channel aspirations, because the time, facilities and budget have been arranged in such a way. The utilization of aspiration funds in the village in Hative Besar has been utilized properly, but there is no transparency with each other regarding the utilization of aspiration funds.